APTIAN TO CAMPANIAN CALCAREOUS NANNOFOSSILS BIOSTRATIGRAPHY FROM THE BOTTACCIONE SECTION, GUBBIO, CENTRAL ITALY - FABRIZIO TREMOLADA (Rivista Italiana di Paleontologia e Stratigrafia, 2002)
Late Aptian-Campanian biostratigraphic investigations performed on calcareous nannofossils provided a refined stratigraphic resolution  of the Scisti a Fucoidi and Scaglia Formations in the Bottaccione section (Umbria-Marche Basin, Central italy). Additional bioevents such as the Last Occurrence (LO) of both Assipetra infracretacea larsonii and Rucinolithus terebrodentarius youngii and the First Occurrences (FOs) of Pararhabdolithus achlyostaurion and large Biscutum constans were detected and might be used to refine the Late Aptian-Albian biostratigraphy at low latitudes.